Diagnosis and Management of Pulmonary Embolism in Pregnancy - Sarah Broder; Peter Paré (Canadian Respiratory Journal)
Pulmonary embolism in pregnancy is a significant and under-recognized problem. In British Columbia, where there are 46,000 pregnancies per year, it is estimated that there are approximately 160 pulmonary embolisms per year and one maternal death every two years secondary to pulmonary embolism. A complete assessment for suspected pulmonary embolus can be performed without putting the fetus at significant risk from radiation exposure. An algorithm is provided for the workup of pulmonary embolus during pregnancy. Heparin is the drug of choice for anticoagulating pregnant women, initially managing the situation with intravenous heparin and then switching to the subcutaneous route given in a bid or tid regimen, aiming to keep the activated partial thromboplastin time 1.5 to 2 times the control. The risks to both the fetus and the mother from anticoagulation during pregnancy are reviewed.